PEMBINAAN AKHLAK MULIA SANTRI PONDOK PESANTREN API AL RIYADLOH KABUPATEN SEMARANG - Aziz, Rizky Maulana (JURNAL AL-QAYYIMAH, 2023)
This research aims to describe the unique phenomenon of fostering noble character at Pondok Pesantren API Al Riyadloh using a qualitative descriptive approach. Involving observation techniques, semi-structured interviews, and documentation, the researcher sought data to identify forms of moral development, such as exemplification, exercises, advice, discipline, praise, and sanctions. The validity of the data was tested using source and technique triangulation. The results indicate that moral development at Pondok Pesantren API Al Riyadloh employs various methods, including exemplification, exercises, and advice as means of internalizing moral values. Discipline, praise, and sanctions are used as instruments for supervision and character formation. Factors supporting moral development include the students' awareness of religious values, their backgrounds, and the leadership roles of the Kiai and teachers. On the other hand, the hindering factors involve the students' egos and their surrounding environment. Student awareness is considered the primary foundation, while individual backgrounds and the role of educational leaders play a crucial role in the development process. This research provides a deep understanding of the dynamics of moral development in Islamic boarding schools, highlighting challenges and potential for further development in the education of moral values.